PERAN AKUPRESUR TERHADAP KADAR HAEMOGLOBIN REMAJA PUTRI DENGAN ANEMIA - Setiawandari Setiawandari; Yefi Marliandiani; Nyna Puspita Ningrum (Jurnal Ilmu Kebidanan, 2022)
Adolescent are nation's assets, young women who experience anemia are at risk of becoming pregnant women with anemia. The high prevalence of iron anemia in adolescent girls in Indonesia requires collaborative interventions. The intervention that has been launched by the government is giving blood tablets (TTD) once a week and once a day for women of childbearing age who are menstruating. The acupressure method is an alternative effort to increase hemoglobin levels in adolescent girls with anemia. In addition to increasing hemoglobin levels, it is also useful in maintaining the immune system. The purpose of this study was to analyze the role of acupressure on hemoglobin levels in adolescent girls with anemia. This research is a true experimental design research using a pre post test control group design. Subjects were divided into 2 groups. In 2 months, Group A received acupressure once a day, Group B received TTD once a week. Before and after the intervention, hemoglobin levels were measured. The degree of anemia is divided into mild anemia (hB 8 g/dl – hB 9.9 g/dl), moderate anemia (hB 6 g/dl – Hb 7.9 g/dl) and severe anemia (hB < 6 g/dl). Almost all of the population had normal hemoglobin levels (86.1%) and only 5 people (13.8%) had mild anemia. After the data collected, it was known that p > ​​0.05. The results of the T test analysis obtained were p = 0.606, it was concluded that there was no significant difference in hemoglobin levels between each group.